The San Diego World's Fairs and Southwestern Memory, 1880-1940 - Bokovoy, Matthew F., 1969- (Book collections on Project MUSE., 2005)
Bokovoy peels back the rhetoric of romance and reveals the legacies of the San Diego World's Fairs to reimagine the Indian and Hispanic Southwest.